MOTIVATIONAL CHARACTERISTICS OF URBAN CYCLISTS: CASE OF TOC AND JGC – SCAM BICYCLE CLUBS - Tb. Adinda Laksmana (ASEAN Journal on Hospitality and Tourism, 2019)
Abstract. Nowadays people aware of the importance of health is growing, one of which is the increasing number of sports enthusiasts. Outdoor sports cycling is one of the activities which is in great demand by urbanites. In addition to health purposes, cycling is a mean to escape from the fatigue of daily routines. The emergence of cycling groups in urban communities is a reflection of the need for exercise while having recreation outdoors. To find out the type of motivation for cycling activities in urban communities, questionnaires were conducted on two cycling communities in Indonesia. They are TOC (Trifold Owner Community) and JGC–SCAM (Jaserco Gowes Club–Serang-Cilegon-Anyer-Merak). The results obtained urban cyclists’ characteristics and motivations. There are various kinds of motivations, ranging from exercise, traveling, reducing the effects of air pollution, saving fuel and avoiding congestion, seeking new experiences and challenges, friendships, to just look for self-actualization.